Sports floor characteristics - Kersting, U. G.; Ismail, S. I. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
In this chapter, the effects of different structural properties of Futsal playing surfaces on the resulting change of direction performance, perceived traction properties, and dynamically measured friction forces are examined in relation to each other. Three types of playing surfaces (area-elastic: AE, point-elastic No. 1: PE1, and point-elastic No. 2: PE2) are investigated in conjunction with a defined Futsal shoe. In the agility test, participants performed significantly better on the point-elastic surfaces (PE1 and PE2) compared to the area-elastic surface (AE) (p < 0.05). Additionally, it was found that the PE2 surface exhibited the highest perceived traction. The results suggest that the significantly higher available friction coefficient explains the improvement in performance and traction perception on the PE2 surface. This successfully demonstrates that the structural difference (AE or PE) of the Futsal playing surface has a significant impact on the change of direction performance of experienced Futsal players and their perceived level of traction and friction properties.